Geoelectrical and seismoelectric mapping of subsurface pollution in a closed landfill near the Tongo Bassa and Ngongue river, Douala Cameroon - Kevin, Zebaze Djuka Mba; Yang, Jidong; Djieto Lordon, Anatole Eugene; Huang, Jianping; Perabi, Clotaire José Pako; Rapheal, Onguene; Dirane, Kengue Ngouene Jocelyn; Ahmed, Mbouemboue Nsangou Moussa (Frontiers in Earth Science, 2024)
Located in Douala V (Cameroon), Makepé Missoké is a lowland area that is influenced by the Tongo Bassa and Ngongué rivers. The site has a closed dumpsite, that operated from the 1975's to 2003 for the disposal and storage of domestic waste produced in Douala. Geoelectric profiling (ERT) coupled with seismoelectric imaging was used to characterize the shallow aquifer of the Douala subbasin and map subsurface pollution. The aquifer geometry, hydraulic characteristics, permeability, lithology and leachate plume extent were determined. Fourteen geoelectrical profiles were deployed between June and August 2018 and March 2019. Along these lines, 49 sets of seismo-electric point data were collected in December 2021. A total of 118 wells drilled (2018) were used to obtain water level and topographic data. This survey enables us to visualize waste infiltration and migration within Makepé. The drilled wells indicate that the main lithologies observed are clay, sandy clay, sand, clayey sand and gravel. The leachate plume observed after processing the electric profiles had a resistivity signature of ≤ 10 Ωm, and high electrical conductivity are observed in some wells. The leachate and migrates within the subsurface along a northwest-southwest trend, where. Ggroundwater pollution is observed through due to leachate infiltration. and This infiltration resulted inthe poor water quality indices in some collected samples.are confirmed to have high electrical conductivity values. This Such pollution is common in unconfined aquifers (< 50 m) due to the absence of a confining layer at the landfill. An increase in resistivity values with depth toward the northeast direction indicates progressive vertical dilution during leachate mineralization. This study integrated geoelectric and seismoelectric tomography with basic water chemistry analysis to effectively characterize the groundwater within the phreatic Quaternary/Mio-Pliocene aquifers of the Douala basin.